1996
DOI: 10.1128/jvi.70.1.133-140.1996
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular retention of surface protein by a hepatitis B virus mutant that releases virion particles

Abstract: In the course of chronic infection, hepatitis B virus mutants can sometimes be found circulating in the serum as the predominant species. One class of such mutants contains in-frame deletions in the S promoter region. By transfecting hepatoma cells with wild-type or mutant viral genomic DNA, we have shown that one such mutant gives rise to extremely small amounts of S transcripts, as expected, and therefore expresses very little of the middle and small surface (viral envelope) proteins that are translated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(55 citation statements)
references
References 33 publications
4
51
0
Order By: Relevance
“…This was first found after introducing artificial triple-point mutations or by studying a natural-occurring 129-bp deletion in the S-promoter. 6,32 Our experiments demonstrated that a single-point mutation located in this motif had a tremendous effect on S-gene regulation, resulting in unusual nuclear and perinuclear localization of viral proteins.…”
Section: Discussionmentioning
confidence: 75%
“…This was first found after introducing artificial triple-point mutations or by studying a natural-occurring 129-bp deletion in the S-promoter. 6,32 Our experiments demonstrated that a single-point mutation located in this motif had a tremendous effect on S-gene regulation, resulting in unusual nuclear and perinuclear localization of viral proteins.…”
Section: Discussionmentioning
confidence: 75%
“…18 Core proteins with internal deletions are able to interact with the wild-type core protein and to form mosaic particles. 19 Finally, deletions in the pre-S1 region may lead to retention of surface proteins in the cell by changing the transcriptional regulation of surface protein expression, [20][21][22] In transgenic mice, HBV surface protein retention is directly toxic to the cell or sensitizes the cell to immune or cytokine-mediated injury. [23][24][25][26][27] Combining the effects of all these types of mutations within 1 virus population or even 1 genome, it is conceivable that the virulence of a corresponding HBV population is increased due to enhanced replication and protein expression as well as retention of virus proteins in the cell.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, we can only speculate on the potential pathogenic importance of secretion-defective variants for the development of fulminant recurrent hepatitis B: It is well known that malfolded or mutated proteins that are not secreted can cause stress in the ER, affecting cellular transcription via intracellular signaling pathways. [44][45][46] Specifically it was shown 29 that accumulation of L-protein in the ER can activate the genes encoding the ER luminal chaperon proteins grp78 and grp94. Thereby retention of the mutant L-and S-proteins in the ER could affect host cell physiology.…”
Section: Discussionmentioning
confidence: 99%
“…This staining pattern is reminiscent of the localization of proteins retained in the ER. [27][28][29] Additional staining with appropriate antibodies for the ER and Golgi compartment revealed a predominant colocalization of all mutant envelope proteins with the perinuclearly localized ER, but not with the Golgi compartment ( Fig. 5).…”
Section: The Mutant Envelope Proteins Showed An Aberrant Subcellularmentioning
confidence: 92%